2022
DOI: 10.5334/aogh.3728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Virtual Networking Event for Emerging Women Leaders in Global Health

Abstract: Background: Networks are critical for leadership development, but not all networks and networking activities are created equally. Women and people of color face unique challenges accessing networks, many of which were exacerbated during the COVID-19 pandemic. Virtual platforms offer opportunities for global professionals to connect and can be better tailored to meet the needs of different groups. As part of the Consortium of Universities for Global Health annual meeting in 2021, we organized a net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Virtual meetings cost little to no time and money for travelling and accommodation, which a previous report insisted were factors favourable for women and persons living in low- and middle-income countries. 2 However, our respondents found in-person meetings to be better in terms of being ‘easy to build friendships’ (90.6%) and ‘having fun’ (77.6%). This was compatible with the previously mentioned results.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Virtual meetings cost little to no time and money for travelling and accommodation, which a previous report insisted were factors favourable for women and persons living in low- and middle-income countries. 2 However, our respondents found in-person meetings to be better in terms of being ‘easy to build friendships’ (90.6%) and ‘having fun’ (77.6%). This was compatible with the previously mentioned results.…”
Section: Discussionmentioning
confidence: 72%
“…However, the two groups showed no significant differences in terms of personal relationship formation and a sense of unity in virtual events. 'Networking' in previous articles usually focused on professional dimensions; 2,7 however, in the present study we presumed that networking events have professional and non-professional dimensions. This study may suggest that participants in virtual networking meetings found that these meetings were better for forming professional relationships than personal relationships.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…There are other approaches to virtual networking, such as virtual events, and contacts made at these events which should also be maintained if you presume the relationship to be beneficial ( Iyengar et al, 2022 ).…”
Section: Building and Maintaining A Networkmentioning
confidence: 99%